Device Thrombosis After Percutaneous Left Atrial Appendage Occlusion Is Related to Patient and Procedural Characteristics but Not to Duration of Postimplantation Dual Antiplatelet Therapy. (March 2018) - Pracon, Radoslaw; Bangalore, Sripal; Dzielinska, Zofia; Konka, Marek; Kepka, Cezary; Kruk, Mariusz; Kaczmarska-Dyrda, Edyta; Petryka-Mazurkiewicz, Joanna; Bujak, Sebastian; Solecki, Mateusz; Pskit, Agnieszka; Dabrowska, Agnieszka; et al.
Abstract : Background—: Device-related thrombus (DRT) after left atrial appendage occlusion is a worrisome finding with little knowledge about when to expect it and how to prevent it. This study sought to investigate correlates of DRT after left atrial appendage occlusion, its time of diagnosis, and particularly, association with postimplantation dual antiplatelet therapy duration. Methods and Results—: Consecutive patients (n=102) after left atrial appendage occlusion with AMPLATZER Cardiac Plug/Amulet (n=59) or WATCHMAN (n=43) were included in a prospective registry (October 2011–May 2016). Follow-up was done at 1.5, 3 to 6, and 12 months postimplantation. DRT was classified as early (at 1.5 month), late (at 3–6 month), or very late (at 12-month follow-up). Postimplantation dual antiplatelet therapy was recommended for 30 to 180 days and decided independently by attending physicians. Final analysis included 99 patients, 42 (42.4%) females, with median CHA2 DS2 -VASc of 4.0 (interquartile range [IQR], 3.0–5.0) and median HAS-BLED score of 2.0 (IQR, 1.0–3.0). DRTs were observed in 7 (7.1%) patients: 2 (28.6%) early, 2 (28.6%) late, and 3 (42.9%) very late. When compared with patients without DRT, those with DRT presented more often with a history of prior thromboembolism (5 [71.4%] versus 28 [30.4%]; P =0.04), had lower left ventricular ejection fraction (50.0 [IQR, 35.0–55.0] versus 60.0 [IQR, 55.0–66.0]; P <0.01), and had greater proportion of patients with deep device implantation (6 [85.7%] versus 36 [39.1%]; P =0.04) and with larger devices implanted (30.0 mm [IQR, 27.0–33.0] versus 25.0 mm [IQR, 24.0–28.0]; P <0.01). Postimplantation dual antiplatelet therapy duration was not different between the 2 groups (12.4 weeks [IQR, 6.0–49.7] with DRT versus 13.0 weeks [IQR, 7.3–26.0] without DRT; P =0.77). Conclusions—: In this real-world series, DRT was observed early, late, and very late after left atrial appendage occlusion. It was related to patient and procedural characteristics but not to postimplantation dual antiplatelet therapy duration.